Research on load-balanced construction algorithm of logical carrying network - Hao-xue WANG; Ming JIANG; Ji FU (Tongxin xuebao)
To improve the extensibility of network service,constructing algorithm of logical carrying network was pro-posed by mapping the demands of network service into substrate network.To solve the problem of construction efficiency,on-demand carrying strategy was introduced to provide different resources to meet different service requirements.Based on available resource and current link load,an improved multi-commodity flow model was proposed to compute the re-source allocation.Simulation results indicate this al ithm can improve network service capability from construction success rate and average construction profit.